Электростатические фильтры дымовых газов тепловых электростанций как нагрузка источников комбинированного электропитания - Богуславский, Леонид Зиновьевич; Диордийчук, Виталий Владимирович (НТУ "ХПИ", 2016)
Рассмотрены вопросы изменения характера нагрузки систем комбинированного питания электростатических фильтров в процессе улавливания пыли с известными значениями удельного электрического сопротивления при формировании слабопроводящего слоя на поверхности осадительного электрода. Установлена взаимосвязь величины напряжения прикладываемого к газовому промежутку с толщиной слоя осевшей пыли, позволяющая судить о интенсивности коронного разряда в данных условиях и режиме работы источника питания постоянного напряжения. Установлен характер изменения электрической емкости электродной системы в зависимости от толщины слоя осевшей пыли.

The article deal with power supply systems for electrostatic precipitators (ESP). The dust removal process lead to dust layer forming on the precipitation electrode of the ESP. The power supply design problems connected with load character changing from active-capacitance type to fully capacitance type due to contamination of the precipitation electrode. The voltage distribution between the dust layer and the gas gap determine the corona discharge mode according to volt-ampere characteristic. The interconnection between voltage on gas gap and thickness of dust layer, which predict the intensity of corona discharge in current conditions, is established. It is easy to model corona's discharge locking effect by using the resulting formula. The electric capacity of electrode system change character in dependency of dust layer thickness is established. The changing of capacity of the electrode system influence on a power of a supply system, which used pulsed ESP energization. The formula for determining the time constant of the electrode system is obtained.
Electrostatic precipitators for exhausts gases of thermal power plants as a load for a combined power source
Keywords: толщина слоя пыли; комбинированное питание; ЭФ; электродная система; коронирующий электрод; dust layer thickness